Microtubule disruption changes endothelial cell mechanics and adhesion - Andreas Weber (Nature Portfolio, 2019)
Abstract The interest in studying the mechanical and adhesive properties of cells has increased in recent years. The cytoskeleton is known to play a key role in cell mechanics. However, the role of the microtubules in shaping cell mechanics is not yet well understood. We have employed Atomic Force Microscopy (AFM) together with confocal fluorescence microscopy to determine the role of microtubules in cytomechanics of Human Umbilical Vein Endothelial Cells (HUVECs). Additionally, the time variation of the adhesion between tip and cell surface was studied. The disruption of microtubules by exposing the cells to two colchicine concentrations was monitored as a function of time. Already, after 30 min of incubation the cells stiffened, their relaxation times increased (lower fluidity) and the adhesion between tip and cell decreased. This was accompanied by cytoskeletal rearrangements, a reduction in cell area and changes in cell shape. Over the whole experimental time, different behavior for the two used concentrations was found while for the control the values remained stable. This study underlines the role of microtubules in shaping endothelial cell mechanics.